FUNGSI PENGAWASAN DPRD TERHADAP PEMERINTAH DAERAH DALAM MEWUJUDKAN APARATUR PEMERINTAH DAERAH YANG BERINTEGRITAS UNTUK KESEJAHTERAAN RAKYAT - Muhammad Arsyi Jailolo; Aminuddin Ilmar; Anshori Ilyas (UNES Law Review, 2023)
This study aims to examine the effectiveness of the supervisory function of the Makassar City DPRD on the performance of the Makassar City Government itself as an ideal variable aspect of regional government administration. This research was conducted at the Makassar City DPRD and Makassar City Government. The time of this research is for two months (February to March 2023). This study uses an empirical-qualitative method and uses primary data collected by giving questions in the form of interviews to respondent representatives from DPRD and Makassar City Government. Furthermore, the method of data analysis was systematically inventoried and then the content material was analyzed using an analytical conceptual approach with qualitative analysis. The results of this study indicate that the substance of the DPRD's oversight function in Makassar City runs with the process of budgeting, legislation, and supervising the enforcement of local regulations. the implementation mechanism is by monitoring evaluation and absorption of community aspirations. The obstacle is that not all DPRD recommendations are implemented by the Makassar City Government. The problem lies in the firmness of human resources in the Makassar City DPRD